Progresso e Civilidade na Athenas Mineira: o debate sobre a instrução pública nas páginas do Jornal O Pharol (1885-1926) - Alves, Suzele Sany Lacerda (2024)
This research linked to the Postgraduate Program in Education – UFU in the line of research, History and Historiography of Education, aimed to analyze how the newspaper Pharol was configured as an agent propagating the ideals of progress and civility in Juiz de Fora and which main representations from the perspective of public instruction were constructed and/or published in the newspaper. The established time frames (1885-1926) initially considered changing the periodicity of publications, which stopped being weekly and became daily, fact that occurred on January 1, 1885 and yet another event that marked the newspaper that same year was the change of property, which came to be owned by Lindolpho de Assis, who gave it a more conservative direction. The end date corresponded to the last year listed in all the newspapers of Pharol digitized in Hemeroteca, 1926. The research problem consisted of understanding what the main ideas were related to education/ public instruction that circulated in Pharol's journalistic articles and which representations related these corroborated with the dissemination of the senses of progress and civility that permeated political debates in the first decades of the republican period in Brazil. To this end, this research sought support in the theoretical approach of Cultural History and in the perspectives of Roger Chartier (1990) for understanding the representations produced and/or reproduced by the newspaper. Progress and civility constituted the “guiding thread” for dialogue between the categories considered by the research, namely, Public Instruction, Illiteracy, Religious Education, Graduate prime school, and School Hygiene. The categories activated in this investigation are justified because they make up the discourses that permeated the theme of Public Instruction in the Pharol and which represented the political and cultural ambience of the period. Jornal Pharol, the main source of this research, He was an enthusiast of progress, his publications, in addition to highlighting Juiz de Fora's virtuous advances in the industrial, commercial and intellectual sectors, they also demanded measures that were in the interest of progress and civilization. Among the singularities of Athenas Mineira, regarding its historical constitution, it appears that immigration was an element that boosted industrialization in the city and influenced its progress, but it also caused great tensions in the religious field, as the large contingent of German immigrants were mostly Protestant. The Pharol disapproved of Catholics' practices of religious intolerance against Protestants, however his position did not place him in a position to defend the Protestant religion, but rather the principles of civility consistent with Eurocentric progress and modernity. In this study, it was possible to ascertain the belief in mass schooling as a panacea and Pharol's participation in the production and reproduction of an imaginary of progress and civility in Juiz de Fora, which considered public education as a means of cultural and moral improvement of the population. The newspaper's “press men” had projection and influence in the Judiciary society, which gave Pharol credibility and notoriety for its publications.